Sistem Notifikasi Untuk Mengurangi Pembatalan Pesanan Di Karang Furniture - Rahmanto, Yogi Nur; Wibowo, Jati Sasongko (Innovative: Journal Of Social Science Research, 2025)
The pre-order (PO)-based furniture industry faces challenges in maintaining effective communication between sellers and buyers, particularly during the production process. This study aims to develop a web-based notification system to enhance communication transparency and reduce the risk of order cancellations. The system is designed using HTML, PHP, and MySQL technologies and manually sends production status notifications via WhatsApp. The implementation of the system at Karang Furniture demonstrates improvements in data management efficiency and buyer communication. System testing using the Black Box Testing method ensures that the features function as required. A 6% reduction in order cancellation rates highlights the positive impact of this system in supporting the PO-based business model.